IMPLEMENTASI PROGRAM MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) DI KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN KOTA PEKANBARU - Zubaidah, Evi; Lubis, Ema Fitri (UIR PRESS, 2018)
This research aims to the implementation of the community empowerment program based on citizens (pmb-rw) in the village of west subdistrict sidomulyo and what constraints encountered in implementing of the community empowerment program based on citizens (pmb-rw) in the village of west subdistrict sidomulyo. The methods used in this research is descriptive, qualitative data collection by way of interviews, observation, and documentation with the (PMB-RW) Program Coordinator-RW Companion Facilitators in the town, in the village, Along the citizens Program PMB Users-RW. The results showed that in terms of the interests that are affected by the policy are enshrined the importance either to the Coordinator of the city and the region, as well as implementing the community users of the program, still less the maximum benefits and changes in get the target because of the program's not all involved in the activity, the position of taking and executing policies were in accordance with the mechanisms and conditions specified. Resources in terms of quality is quite adequate but felt less in terms of quantity. Obstacles encountered is in terms of understanding the society and communication is lacking. So too with the realization of the activities budget less.